2023
DOI: 10.1111/cns.14193
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolic signatures in patients with genetic and nongenetic amyotrophic lateral sclerosis

Abstract: Aims To study the brain metabolic signature in Chinese amyotrophic lateral sclerosis (ALS) patients and compare the difference in brain metabolic patterns between ALS with and without genetic variants. Methods We included 146 patients with ALS and 128 healthy controls (HCs). All patients with ALS underwent genetic testing to screen for ALS related genetic variants and were then divided into genetic (n = 22) and nongenetic ALS (n = 93) subgroups. All participants underwent brain 18F‐FDG‐PET scans. Group compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…In contrast, some studies have reported decreased FC in the left and right cerebellar lobule VI in ALS participants 302,303 . Additionally, studies have investigated metabolic levels in the cerebellum of ALS patients, although the findings remain inconsistent 304–307 …”
Section: Cerebellum and Other Ndsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some studies have reported decreased FC in the left and right cerebellar lobule VI in ALS participants 302,303 . Additionally, studies have investigated metabolic levels in the cerebellum of ALS patients, although the findings remain inconsistent 304–307 …”
Section: Cerebellum and Other Ndsmentioning
confidence: 99%
“…302,303 Additionally, studies have investigated metabolic levels in the cerebellum of ALS patients, although the findings remain inconsistent. [304][305][306][307]…”
Section: Cerebellum and Alsmentioning
confidence: 99%
“…In addition to the discussion of variable regions above, there was a study by Liu et al that appears to flip the commonly seen metabolic pattern in ALS. In this study, hypometabolism was found in the cerebellum and midbrain, while hypermetabolism was observed in the anterior cingulate and the prefrontal lobe [ 36 ]. This is a pattern much different from what other studies have found.…”
Section: Application Of Various Pet Probes In Alsmentioning
confidence: 99%
“… The structure of [ 18 F]FDG, which has uncovered a specific signature of glucose hypermetabolism and hypometabolism in ALS, along with being applied to a number of other purposes [ 18 34 , 36 38 , 42 47 ]. …”
Section: Figurementioning
confidence: 99%